Mechanisms of traumatic injury to the shoulder girdle in the Australian Football League. Issue 9 (September 2019) - Schwab, Laura M.; McGrath, Tim; Franettovich Smith, Melinda M.; Mendis, M. Dilani; McGhee, Deirdre; Hides, Julie
Abstract: Objective: To investigate mechanisms of shoulder girdle injuries and their impact on players from the Australian Football League (AFL). Design: Retrospective video analysis. Methods: Two experienced sports physiotherapists (>10 years) examined video footage of shoulder complex injuries that occurred in the 2015 premiership season. Information obtained from video footage included activity prior to injury; mechanism of injury; arm, head and neck position and point of body contact at the time of injury. Player demographics and injury characteristics were obtained from club and media data. Results: The most common mechanism of injury was lateral contact (34.6%) followed by hyperflexion/ abduction of the shoulder (19.2%). Glenohumeral joint (GHJ) dislocations and subluxations were the most frequent diagnosis for all mechanisms of injury, and occurred in a variety of shoulder positions. Over 80% of injuries occurred with the arm below 100° of shoulder flexion or abduction. The most common activity prior to injury was 'ball in dispute' (34.6%). Lateral contact injuries had the highest overall severity (two-thirds of players missed >3 games) and over 50% of shoulder injuries required surgery. Players missed on average 5.1 season games due to shoulder injury. Conclusion: The lateral contact mechanism was the most common and severe mechanism of shoulder injury. Improved understanding of shoulder girdle injury mechanisms can help guide the use of preventative strategies and injury management programs in elite AFL players.